The Urgency of the History of Islamic Civilization Course in the Islamic Psychology Study Program - Devia purwaningrum; Dessy Farantika; arif muzayin Shofwan (Universitas Nahdlatul Ulama Blitar, 2022)
Nahdlatul Ulama University Blitar includes the History of Islamic Civilization course as a compulsory subject, especially for institutions affiliated with Islamic religious universities, both public and private throughout Indonesia, including the Islamic Psychology study program. This descriptive qualitative research through literature study with content analysis discusses the urgency of the History of Islamic Civilization course in the Islamic Psychology study program at Nahdlatul Ulama University Blitar. This research found the following three things, among others: First, one of the objectives of studying the history of Islamic civilization is to explore and review the factors that led to the progress of Islam in the field of civilization and what factors caused its decline; Second, the benefits of studying the history of Islamic civilization include educational benefits, social benefits, and predictive benefits; Third, the driving force in studying the history of Islamic civilization is the knowledge contained in the Quran Surah Ali Imran: 190-192; Quran Surah Al-Mujadalah: 11; Quran Surah Bani Israel: 36; Quran Surah Al-Qashash: 77; Quran Surah Ali Imran: 97; Quran Surah Al-Hajj: 46; Quran Surah Az-Zumar: 17-18; and Hadith narrated by Bukhari Muslim